Global, regional, and national burden of pediatric nasopharyngeal carcinoma (1990–2021) and projections of future disease burden trends - Xu, Yilong; Dai, Huaqiang; Chen, Qiuyu; Xu, Yanling; Xu, Yanyu; Dai, Sihai; Hong, Mingyan (Frontiers in Pediatrics, 2025)
ObjectivePediatric nasopharyngeal carcinoma (NPC) is an exceedingly rare and often overlooked disease. However, early detection of this condition is a decisive factor in its prognosis. This study aims to quantify the disease burden and epidemiological trends of pediatric nasopharyngeal carcinoma over a 30-year period (1991–2021) and provide projections for future disease burden.MethodsComprehensive data on pediatric NPC from 1990 to 2021 were obtained from the Global Burden of Disease study. This dataset includes information on the incidence of pediatric NPC, disaggregated by gender. The Joinpoint regression model was used to identify turning points in epidemiological trends, while decomposition analysis helped identify the factors driving these trends. To forecast future incidence rates, the Norpred model were applied.ResultsIn 1990, the estimated global number of pediatric NPC cases was 1,269 (1,119–1,422), with 764 (663–892) cases in boys and 505 (427–592) cases in girls. The global ASIR of pediatric NPC in 1990 was 0.07 (0.06–0.08), with rates of 0.09 (0.07–0.10) in boys and 0.06 (0.05–0.07) in girls. By 2021, the estimated global number of pediatric NPC cases decreased to 966 (796–1,152), including 576 (444–725) cases in boys and 390 (326–501) cases in girls. The global ASIR of pediatric NPC in 2021 was 0.05 (0.04–0.06), with rates of 0.06 (0.04–0.07) in boys and 0.04 (0.03–0.05) in girls. Joinpoint regression analysis indicated stable epidemiological trends from 1990 to 2021, with a slight decline in both sexes. Based on the Nordpred model, the projected 2046 ASIR for pediatric NPC is 0.09 (male: 0.10; female: 0.80), with 1,169 total cases (boys: 680; girls: 489).ConclusionThe incidence of pediatric NPC is relatively low overall, with a slight downward trend in its epidemiological trajectory.